2018
DOI: 10.3390/children5090124
|View full text |Cite
|
Sign up to set email alerts
|

First Aid Practices and Health-Seeking Behaviors of Caregivers for Unintentional Childhood Injuries in Ujjain, India: A Community-Based Cross-Sectional Study

Abstract: Data on types of community first aid use and treatment provided post-injury from many low‒middle-income countries, including India, are lacking. This cross-sectional study was conducted among children aged one month to 18 years of age, in Ujjain, India, to understand types of first aid given and health-seeking post-injury. A total of 1087 injuries in 1049 children were identified in the past year. A total of 729 (67%) injured children received first aid and 758 (70%) sought some form of health care. Children w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
2
6
0
1
Order By: Relevance
“…The results of this study are in line with previous findings, a study of 729 respondents found that the substances most often used in first aid burns were coconut oil (44%), antiseptic cream (25%), and toothpaste (22%) (Pathak et al, 2018). Some household products that are often used are toothpaste, butter, ink, sugar water, soy sauce, oil, honey, eggs, mashed potatoes, and ice (Graham, H.E., et al, 2012).…”
Section: Local Materials Used As a Topical Medication For Burnssupporting
confidence: 91%
“…The results of this study are in line with previous findings, a study of 729 respondents found that the substances most often used in first aid burns were coconut oil (44%), antiseptic cream (25%), and toothpaste (22%) (Pathak et al, 2018). Some household products that are often used are toothpaste, butter, ink, sugar water, soy sauce, oil, honey, eggs, mashed potatoes, and ice (Graham, H.E., et al, 2012).…”
Section: Local Materials Used As a Topical Medication For Burnssupporting
confidence: 91%
“…Nine studies reported the knowledge of burn first aid (2 Saudi Arabian studies 15,27 used Internet-based survey in general population), whereas 19 studies reported first aid substances applied in burn patients. Twelve studies were conducted in Africa, 3,4,6,7,[11][12][13][14]17,23,29,30 7 in the Middle East, 9,10,15,16,25,27,28 3 in India, 18,19,26 and 1 in the United States and United Kingdom, 20 Australia, 8 Pakistan, 21 China, 22 Cambodia, 5 and Malaysia 24 each. Among the included studies, water irrigation was administered in only 29% of the population, whereas 46% administered various traditional materials, and 30% did not administer first aid at all.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-eight studies were included in the review, with a total of 20,150 subjects (Table 1). 3–30 Twenty-five studies were cross-sectional or survey studies, with only 1 quasi-experimental, 9 1 prospective cohort, 13 and 1 mixed-methods study 23 . Only 19 studies performed statistical analysis, all of which analyzed different outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Penatalaksanaan yang cepat dan tepat dapat mencegah kematian dan dapat mempertahankan kelangsungan hidup. Kelangsungan hidup bisa dicapai sampai 95% (3).…”
Section: Pendahuluanunclassified